Zika virus and microcephaly in Southeast Asia: A cause for concern?. Issue 1 (January 2020) - Kuadkitkan, Atichat; Wikan, Nitwara; Sornjai, Wannapa; Smith, Duncan R.
Abstract: Zika virus (ZIKV), a mosquito transmitted virus in the family Flaviviridae, genus Flavivirus, recently emerged to cause infections in more than 70 countries and territories around the world. While human infection is normally asymptomatic, it can also result in a mild febrile disease similar to dengue fever. However, when a pregnant woman is infected, ZIKV can cause fetal abnormalities including microcephaly. Evidence has suggested that ZIKV has circulated in Southeast Asia for more than a decade and yet cases of ZIKV associated microcephaly remain sparsely documented. This review seeks to collate the information currently existing on ZIKV associated microcephaly in Southeast Asia, and assess the potential future risk posed by this virus.